A practical guide to small angle X‐ray scattering (SAXS) of flexible and intrinsically disordered proteins. Issue 19 (29th August 2015) - Kikhney, Alexey G.; Svergun, Dmitri I.
Abstract : Small‐angle X‐ray scattering (SAXS) is a biophysical method to study the overall shape and structural transitions of biological macromolecules in solution. SAXS provides low resolution information on the shape, conformation and assembly state of proteins, nucleic acids and various macromolecular complexes. The technique also offers powerful means for the quantitative analysis of flexible systems, including intrinsically disordered proteins (IDPs). Here, the basic principles of SAXS are presented, and profits and pitfalls of the characterization of multidomain flexible proteins and IDPs using SAXS are discussed from the practical point of view. Examples of the synergistic use of SAXS with high resolution methods like X‐ray crystallography and nuclear magnetic resonance (NMR), as well as other experimental and in silico techniques to characterize completely, or partially unstructured proteins, are presented.